Prevalence of cryptococcosis in Atlántico, department of Colombia assessed with an active epidemiological search - María Clara Noguera; Patricia Escandón; Merle Arévalo; Yina García; Luz Estela Suárez; Elizabeth Castañeda (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION Cryptococcosis is the second most frequent cause of opportunistic infections in human immunodeficiency virus (HIV) patients in Colombia. We aimed to determine the prevalence of cryptococcosis in the Colombian department of Atlántico. METHODS An active search for cryptococcosis cases was conducted between 2015 and 2017 in health institutions by distributing surveys to clinicians and characterizing samples phenotypically and genotypically. RESULTS Thirty-eight cryptococcosis cases were identified (81.6% men, 76.3% HIV patients). The calculated annual prevalence was 5.08/1 million inhabitants. Cryptococcus neoformans var. grubii VNI was isolated in 34 cases. CONCLUSIONS These results provide the basis for passive surveillance of cryptococcosis.